2016
DOI: 10.32598/jccnc.2.2.103
|View full text |Cite
|
Sign up to set email alerts
|

Age–Friendly Cities Features From the Elderly’s Perspectives Underscoring “Community Support and Health Services”

Abstract: Background: The 21 st century is characterized by two challenges; 1) Urbanized population, 2) Ageing population. In this regard, the Iranian old population ages over 60 years is expected to grow rapidly. Improving the elderly's quality of life is one of the challenges for policymakers and achieving this goal is accessible by designing accurate plans. In this way, WHO has initiated a global project to define "age-friendly cities." This study aims to evaluate the criteria of agefriendly cities from the elderly's… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 11 publications
0
10
0
Order By: Relevance
“…According to the results, the mean and standard deviation of scores in the outdoor spaces and buildings indicator was 31.58 ± 2.504. based on the elderly's point of view, the highest and lowest scores, was given to the “Pavements are well-maintained, smooth, level, non-slip, and wide enough to accommodate wheelchairs with low curbs that taper off to the road “and” Pedestrian crossing lights allow sufficient time for elderly people to cross the road and have audio signals, respectively [ Table 1 ]. [ 15 16 ]…”
Section: Resultsmentioning
confidence: 99%
“…According to the results, the mean and standard deviation of scores in the outdoor spaces and buildings indicator was 31.58 ± 2.504. based on the elderly's point of view, the highest and lowest scores, was given to the “Pavements are well-maintained, smooth, level, non-slip, and wide enough to accommodate wheelchairs with low curbs that taper off to the road “and” Pedestrian crossing lights allow sufficient time for elderly people to cross the road and have audio signals, respectively [ Table 1 ]. [ 15 16 ]…”
Section: Resultsmentioning
confidence: 99%
“…Providing spaces for socialization, community resorts, places to chat, and places to accompany elders are considered as the essential factors for the elderly people. Large resorts in urban spaces too had appeared in previous literature as a significant feature [14]. Moreover, taking note of old and nostalgic elements in such spaces help them have a deeper sense of belonging.…”
Section: Discussionmentioning
confidence: 99%
“…Iran is experiencing a rapid momentum in population aging. This population constituted (≥65) made 20% of the total population in 2016, and the statistical predictions refer to a 25% growth by 2025 (14). To conduct the semi-structured interviews, participants are selected with respect to the maximum variation of age, literacy, gender, and self-rated health.…”
Section: -1-1 -Sampling and Data Collectionmentioning
confidence: 99%
See 1 more Smart Citation
“…Despite the importance of such services, most of the research and practice in South Korea has emphasized various aspects of urbanization and the physical space of the buildings [3]. While some international studies have addressed age-friendly city features from the perspective of older adults, which underscores CSHS [9,10], no research has been conducted with a focus on CSHS in South Korea. Moreover, although a few domestic studies have been conducted which have reported older adults' perceptions of the age-friendliness of cities [7,11], they did not specifically concentrate on older adults' perceptions of CSHS.…”
Section: Community Support and Health Services As Amentioning
confidence: 99%